Asuhan Kebidanan pada Ny. M dengan Luka Perineum Menggunakan Daun Binahong pada Masa Postpartum di Pmb Bd. Silvi Ayu, S. Keb - Khoiri Zahrotil Hayati; Ayu Wandira Br Ginting; Desi Kusumawati; Noviyanti Noviyanti; Yessi Azwar; Tengku Silahwati Ningsih; Dwi Sapta Aryantiningsih; Donny Hendra; Yunni Safitri; Cindy Febriyeni; Siti Zakiah (Pusat Riset dan Inovasi Nasional, 2026)
The postpartum period is a crucial phase for mothers to recover after childbirth. One of the common problems is perineal wounds, caused either by episiotomy or spontaneous rupture, which require proper care to prevent infection and accelerate healing. This case study aimed to provide midwifery care for Mrs. M, 28 years old, P3A0H3, with a second-degree perineal wound at PMB Bd. Silvi Ayu, S.Keb. The SOAP approach was applied through assessment, diagnosis, intervention, implementation, and evaluation over five days (June 12–16, 2025). Interventions included education on perineal hygiene, encouragement of nutritious food intake, light mobilization, and perineal wound care using boiled binahong leaves. The results showed decreased pain, reduced edema, a dry wound, and complete healing on the fifth day, with the REEDA score decreasing from 11 to 0. The discussion emphasized that flavonoids, saponins, and ascorbic acid in binahong leaves contribute to tissue regeneration and faster healing. Limitations of this study included the short monitoring period, limited sample, and reliance on maternal compliance. In conclusion, binahong leaf decoction was found to be effective, practical, and able to enhance maternal independence in wound care. This study is expected to serve as a reference for midwifery practice and as a basis for further research with a wider scope.